2020
DOI: 10.1111/jam.14802
|View full text |Cite
|
Sign up to set email alerts
|

Survival and infectivity of Toxoplasma gondii and Cryptosporidium parvum oocysts bioaccumulated by Dreissena polymorpha

Abstract: Aims The study was aimed to understand the depuration process of Cryptosporidium parvum and Toxoplasma gondii oocysts by zebra mussel (Dreissena polymorpha), to consider the use of the zebra mussel as a bioremediation tool. Materials and methods Two experiments were performed: (i) individual exposure of mussel to investigate oocyst transfers between bivalves and water and (ii) in vivo exposure to assess the ability of the zebra mussel to degrade oocysts. Results (i) Our results highlighted a transfer of oocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Diseases caused by eating shellfish have been increasing worldwide. Several epidemics associated with eating bivalve foods have been documented ( Bigot-Clivot et al, 2022 ; DeMone et al, 2020 ; Géba et al, 2021 ; Ligda et al, 2020 ; Manore et al, 2020 ; Potasman et al, 2002 ; Santos et al, 2018 ; Willis et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diseases caused by eating shellfish have been increasing worldwide. Several epidemics associated with eating bivalve foods have been documented ( Bigot-Clivot et al, 2022 ; DeMone et al, 2020 ; Géba et al, 2021 ; Ligda et al, 2020 ; Manore et al, 2020 ; Potasman et al, 2002 ; Santos et al, 2018 ; Willis et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cercarial dilution effect with D. polymorpha is not as spectacular as in the case of P. acuta, but taking into account the huge densities of dreissenid population achieved in the environment [66], it seems to us that D. polymorpha may play the role of an important dilution of the freeswimming larval stages in the natural system. Moreover, D. polymorpha also collects oocysts, cysts and spores of various species dangerous to humans [67][68][69][70][71]. In general, research about the use of different species of bivalve molluscs as pathogen collectors indicates the usefulness of these organisms for the dilution effect of parasite propagules [38,[72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems quite astonishing that the used filter feeder-D. polymorpha-which feed without reaching saturation [77], did not remove the greater number of cercariae. Géba et al [71] showed that parasite oocysts can be bioaccumulated in the tissues of D. polymorpha, but can also be partially released via pseudofaeces. Gopko et al [78] showed that the filter feeder Anodonta anatina (L.) (Bivalvia: Unionidae) effectively removed the furcocercariae of Diplostomum pseudospathaceum (Digenea: Diplostomatidae) from the water, but they suggest that the cercariae are probably transformed into pseudofeces and poorly ingested, similar to the studies presented by Bontes et al [79] with the use of similar-sized filamentous cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Mussel filtration concentrates their numbers, often proportionally to their values in the water, allowing usage of the bivalve’s tissues as indicators and a good integrative matrix for biomonitoring of these pathogens (Lucy et al, 2008 , 2010 ; Lucy, 2009 ; Conn et al, 2014 ; Ladeiro et al, 2014 ; Gomes et al, 2018 ; Géba et al, 2020 ). In addition, due to the digestion of C. parvum and T. gondii oocysts, mussels can be used as a bioremediation tool to mitigate contamination by pathogenic protists (Géba et al, 2021a , b ). Zebra mussels were found useful in assessing viral contamination by measuring the accumulation of indicators of viral pollution F-specific RNA bacteriophages in their tissue (Capizzi-Banas et al, 2021 ).…”
Section: Regulating and Supporting/maintenancementioning
confidence: 99%